Legal Protection for Patient of Independent National Health Insurance’s Participant: Restriction on Hospitalization Upgrade - I Nyoman Sudastra; Mokhamad Khoirul Huda; Asmuni (Jurnal Hukum Prasada, 2020)
The government issued Regulation of the Minister of Health Number 51 of 2018 which regulates the increase in inpatient classes which are difficult to understand. After the issuance of the Minister of Health's regulation regarding the imposition of fees and the difference in costs in the Health Insurance program, causing confusion in the community. This study aims to analyze the legal protection for independent national Health Insurance Participants after the issuance of the Minister of Health Regulation concerning imposition of cost and difference in the health insurance Program. In addition, to analyze the existence of a norm conflict between the Minister of Health Regulation about Imposition of cost and Difference in cost toward the laws and regulations above. This study uses a statutory, conceptual and comparative approach. The type of research used in this study is normative legal research. The results showed that the legal protection of JKN participants independently after the enactment of Permenkes Number 51 of 2018 regarding the Imposition of Costs and Difference in Costs in the Health Insurance Program was unclear and caused legal uncertainty. Besides that, it turns out there has been a norm conflict between the Minister of Health Imposition of Imposition of costs and costs difference in Health Insurance with the Perpres Health Insurance, the National Social Security Act, the Consumer Protection Law and Human Rights. Settlement that can be taken to harmonize the norm conflict is to revoke Article 10 paragraph (5) Permenkes Number 51 of 2018, set aside the Article and conduct a judicial review to the Supreme Court.